2017
DOI: 10.1002/joc.5208
|View full text |Cite
|
Sign up to set email alerts
|

ENSO influence on the interannual variability of the Red Sea convergence zone and associated rainfall

Abstract: The Red Sea convergence zone (RSCZ) is formed by opposite surface winds blowing from northwest to southeast directions at around 18 ∘ -19 ∘ N between October and January. A reverse-oriented, low-level monsoon trough at 850 hPa, known as the Red Sea trough (RST), transfers moisture from the southern Red Sea to RSCZ. The positions of the RSCZ and RST and the intensity of the RST have been identified as important factors in modulating weather and climatic conditions across the Middle East. Here, we investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 51 publications
0
55
1
Order By: Relevance
“…The surface wind anomalies in the southern Red Sea associated with El Niño are counter to the mean local wind field, and thus serve to reduce surface heat fluxes and warm SST. This result is quite the opposite of that found by Dasari et al (2017), who found an increase in the southeasterly wind over the southern Red Sea for a composite El Niño event. However, there are a number of important differences in the methods and data sets used, particularly a focus on a different season as the present analysis.…”
Section: Journal Of Geophysical Research: Oceanscontrasting
confidence: 99%
See 1 more Smart Citation
“…The surface wind anomalies in the southern Red Sea associated with El Niño are counter to the mean local wind field, and thus serve to reduce surface heat fluxes and warm SST. This result is quite the opposite of that found by Dasari et al (2017), who found an increase in the southeasterly wind over the southern Red Sea for a composite El Niño event. However, there are a number of important differences in the methods and data sets used, particularly a focus on a different season as the present analysis.…”
Section: Journal Of Geophysical Research: Oceanscontrasting
confidence: 99%
“…They found that heat fluxes in the northern Red Sea appeared to be modulated by the NAO, East Atlantic/Western Russia (EAWR) pattern and Indian Monsoon Index (IMI), especially during winter and that ENSO was most influential in the southern Red Sea (Abualnaja et al, ). Raitsos et al () and Dasari et al () examined the influence of ENSO on the low‐level wind field in the Red Sea region with attention to the so‐called Red Sea Convergence Zone (RSCZ) and Red Sea Trough (RST), showing that ENSO modulates the position of the RSCZ/RST system with an accompanying adjustment of the scale of the winds blowing along the major axis of the Red Sea.…”
Section: Introductionmentioning
confidence: 99%
“…Wind forcing strongly influences the Red Sea circulation [Patzert, 1974;Quadfasel and Baudner, 1993;Clifford et al, 1997;Eshel and Naik, 1997;Sofianos and Johns, 2003;Yao et al, 2014aYao et al, ,2014b. During winter when winds in the southern half of the Red Sea are southerly, the location of the convergence zone between northerlies and southerlies in the central Red Sea plays a crucial role in the forcing of Red Sea circulation and waves [Langodan et al, 2015;Dasari et al, 2017]. Although northwest winds prevail over our study throughout the year, southeast winds are dominant in the southern Journal of Geophysical Research: Oceans…”
Section: The Winter-summer Shift In the Crsmentioning
confidence: 78%
“…Dasari et al . () also found an impact of the ENSO on the interannual variability of the Red Sea convergence zone and associated rainfall, denoting an increase of southeasterly winds (20–30%) over the southern Red Sea and a decrease of northwesterly winds (10–15%) over the northern Red Sea under El Niño phases. Trends shown by atmospheric circulation modes might be associated with the observed trends in wind speed.…”
Section: Discussionmentioning
confidence: 89%